BREEDING PRACTICE, TRAIT PREFERENCES AND FLOCK STRUCTURE OF LOCAL SHEEP IN SELECTED DISTRICTS OF HADIYA ZONE, SOUTHERN ETHIOPIA: INPUT TO DESIGN COMMUNITY-BASED BREEDING APPROACHES - HEMACHA, SELAMU ABRAHAM; ABATE, MULUGETA KEBAMO; ABOSE, DEGINAT HAILEMESKEL; SHAMEBO, BEREKET TAGESSE; WORKU, TESFAYE WOLDE; KUKORE, WONDIMU TAMRAT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The present study was designed to identify breeding practices, trait preference and flock composition of local sheep in Duna and Misha districts of Hadiya Zone, Southern Ethiopia. A total of 180 respondents were interviewed using structured questionnaire to collect desired data. Group discussions were held in each district to articulate rank of traits of interest. Index values and descriptive statistics were employed to describe collected data. Mating practice was mostly uncontrolled (83%) and aims of sheep production were revenue generation, asset building and meat production with index values of 0.54, 0.36 and 0.10, respectively. Body size was ranked as primary selection criteria for ewe and ram with index values of 0.35 and 0.33, respectively. Considering/giving more weight for mothering ability could make a better genetic advantage due to its good correlation with growth and pre-weaning lamb survival. Therefore, designing breeding program ought to be based on full involvement local farmers.